Precision education governance and the high risks of fabrication of future-orientated learning human kinds - Daniel Nehring (Research Papers in Education, 2023)
Education governance is shifting towards more individually and personally tailored governance, to pre-empt futures to manage the present. Managing the present requires the fabrication of a specifictype of future-oriented learning human kinds. Economically driven imperatives, strengthening transnational stakeholder networks and advances in the life and behavioural sciences are important parts of this shift while transforming the aims, content and methods of education. In terms of fabrication in the neoliberal ethos, structural problems tend to be considered to be products of innate and quan- tified differences in behaviour, competencies, skills and capacities. Furthermore, global, national and local changes entail even tighter economically driven governance. These changes have far-reaching implications. To date, these changes in education governance have been studied separately. By bringing together the current and emerging changes in education governance, in this paper the argument is for a new constitution: precision education governance in the fabrication of future-oriented learning human kinds.